The effect of tennis match play on joint range of motion in junior players - Rok Šrimpf; Tjaša Filipčič; Aleš Filipčič (Palacký University Olomouc, 2019)
Background: Tennis players perform a large number of multidirectional and cutting movements, together with asymmetrical rotational motions resulting from serves and groundstrokes. Numerous shot repetitions and multidirectional motions directly influence a tennis player's upper and lower extremity joint range of motion (ROM). Objective: This study evaluated the changes in the range of motion of junior tennis players before and after match play. Methods: Twelve male (age 14.4 ± 1.3 years) and twelve female (age 13.4 ± 2.1 years) junior tennis players participated in the study. Two skilled experts performed 13 tests to measure passive range of motion of the dominant and non-dominant shoulder, elbow, wrist, hip, knee, and subtalar joints, before and after match play. The t-test and Wilcoxon test were used to determine the differences between the ROM before and after the tennis match, and the differences between the dominant and non-dominant sides of the body. Results: Bilateral measurement of the internal rotation of the shoulder joints, forearm pronation, and inversion of the subtalar joints before match play, show significant differences between extremities, similarly as the elevation of the arm in the coronal plane and forearm pronation, after a tennis match, were also found to display statistically significant differences. ROM values were higher for the internal rotation of both shoulders, external rotation of the non-dominant shoulder, elevation of the arms in the coronal plane, flexion in the elbow joints, pronation in the forearms, adduction in the hips, as well as eversion and inversion of the subtalar joints. Conclusions: Male and female junior tennis players increase their joint ROM during match play through motions which are involved in the execution of tennis shots and tennis movement patterns. Tennis matches that last 90 minutes or less do not have a negative impact on the flexibility of young tennis players.